2014
DOI: 10.1186/1751-0147-56-34
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous estradiol improves shell strength in laying hens at the end of the laying period

Abstract: BackgroundCracked shells, due to age related reduction of shell quality, are a costly problem for the industry. Parallel to reduced shell quality the skeleton becomes brittle resulting in bone fractures. Calcium, a main prerequisite for both eggshell and bone, is regulated by estrogen in a complex manner. The effects of estrogen, given in a low continuous dose, were studied regarding factors involved in age related changes in shell quality and bone strength of laying hens. A pellet containing 0.385 mg estradio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Interestingly, similar to MT2, GnIHR was also found to be expressed in both the thecal and granulosa layers32. It has been reported that E2 secretion and GnIHR expression regulate egg production and quality33343536. GnIHR is mainly expressed in the pituitary.…”
Section: Discussionmentioning
confidence: 89%
“…Interestingly, similar to MT2, GnIHR was also found to be expressed in both the thecal and granulosa layers32. It has been reported that E2 secretion and GnIHR expression regulate egg production and quality33343536. GnIHR is mainly expressed in the pituitary.…”
Section: Discussionmentioning
confidence: 89%
“…Some reports demonstrated the paradoxical role of estradiol in affecting eggshell quality. For example, injecting pellets of estradiol 3-benzoate subcutaneously in laying hens was reported to increase shell thickness and improve shell deformation (Wistedt et al, 2014). In contrast, an injection of 0.5-5 ng g −1 diethylstilbestrol (DES) into the yolk before incubation decreased later egg weight, shell strength and thickness, which accompanied abnormal development of the oviducts after sexual maturation (Kamata et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Dick et al (2003) found that in membrane vesicle preparations from renal distal tubule cells 17beta estradiol, testosterone and dihydrotestosterone increased PMCA activity after 24 h, but not after 1 or 5 h of exposure. In a study on the effects of exogenous estradiol on shell strength in laying hens, Wistedt et al (2014) observed that the hormone had no regulatory effect on PMCA activity in the duodenum and shell gland. If one thinks about it, PMCAs are not the best site for controlling Ca 2+ -extrusion from cells if they would pump the excess Ca 2+ into the blood, thereby increasing the toxic transmembrane Ca 2+ -gradient for all cells.…”
Section: Pmcasmentioning
confidence: 97%